Transformasi Paradigmatik Pendidikan Agama Kristen di Era Digital dalam Pembentukan Karakter Remaja: Perspektif Teologis-Pedagogis - Melisya Ubwarin; Yeremia Hia (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2026)
The paradigmatic transformation of Christian Religious Education (CRE) in the digital era has become a crucial issue to be examined because the development of information technology, virtual culture, and globalization has brought significant changes to adolescents’ mindsets, behaviors, and character formation. These conditions have created various moral and spiritual challenges, such as identity crises, declining ethical sensitivity, and the increasing influence of individualistic and hedonistic values among young people. This study aims to analyze the paradigm transformation of Christian Religious Education in shaping adolescent character through a theological-pedagogical perspective that is relevant to the context of the digital era. The research employs a qualitative method using a library research approach and descriptive analysis of various scientific, theological, and pedagogical sources related to Christian education, teacher spirituality, and adolescent character development in the digital age. The findings indicate that the transformation of the CRE paradigm should be directed toward contextual, participatory, and transformative learning by positioning teachers as spiritual role models and facilitators of character formation. Furthermore, the integration of Christian values, the ethical use of technology, and collaboration among schools, families, and churches are important factors in shaping adolescents who possess strong character, integrity, and spiritual maturity amid increasingly complex digital challenges.